American Muslim Women, Religious Authority, and Activism - Juliane Hammer (University of Texas Press, 2012)
The research project this book is based on was initially not about the womanled prayer at all. A broader interest in the intellectual production of Ameritogether with a long- standing interest in gender debates and women’s roles in Muslim societies. The result was a growing collection of texts written and published by American Muslim women. Two categories of texts emerged: (1) academic writings by Muslim women concerned with Muslim women and gender discourses; and (2) narrative and autobiographical materials. Some of the texts were products of the 1980s and 1990s. However, the bulk of the materials were published in the past decade, with a notable increase in quantity since 2001. It is easy and tempting to explain this surge with the events of September 11, 2001, but that may be too easy. It has become commonplace to describe 9/11 as a formative event not only for the world or the United States but also, and in particular, for American Muslims. And it is certainly the case that the aftermath of 9/11 saw increased scrutiny and indeed often collective persecution of American Muslims as internal security risks while also dramatically increasing interest in all things Islamic and Muslim, both in the American public sphere and in the world of academic inquiry. The growing academic interest (and its marketability) is amply demonstrated by the large volume of recent publications dedicated specifically to the study of American Muslims. Some of these academic works support the impression that 9/11 has forever changed the status of American Muslims in American society, as well as American Muslim attitudes, discourses, and practices. However, many of the debates and issues catapulted to the forefront of public interest and indeed many of the transformation processes that have taken place in American Muslim communities have trajectories that reach farther back and cannot solely be explained by the impact of 9/11. The existence of materials and texts by and about Muslim women dating to the early 1980s is a clear indication of this trend. The increase in the number of texts is more closely linked to increased public and publishing interest than to the absence or insignificance of gender discourses and transformations in the decades before 2001.